Hearing Improvement in Interposition Ossiculoplasty and Myringostapediopexy - Chaudhary, Shashank (Indian J Otolaryngol Head Neck Surg, 2018)
Chronic otitis media (COM) may lead to partial or complete loss of tympanic membrane and erosion of the ossicles. Ossicular chain reconstruction may be done by interposition ossiculoplasty or myringostapediopexy. The aim of our study was to determine the hearing outcome in interposition ossiculoplasty and myringostapediopexy using autologous incus or cortical bone graft in intact canal wall tympanoplasty. 64 patients with COM, who underwent interposition ossiculoplasty or myringostapediopexy were included in the study. Audiometric evaluation was done after 3 months after surgery and all patients were followed up for a period of 1 year. The hearing results were compared in terms of mean pre-op and post-op Air conduction thresholds, Air-Bone gap (ABG) and hearing gain or ABG closure. In this study the mean ABG closure for interposition ossiculoplasty and myringostapediopexy was 15.4 dB and 21.8 dB, respectively. Hearing gain with cortical bone graft was higher than hearing gains with incus in both the groups, but not statistically significant. Myringostapediopexy provides marginally better hearing gain compared to interposition ossiculoplasty. Aulogous incus, and cortical bone graft are suitable autologous materials for ossicular reconstruction and provide similar hearing outcome.